2016
DOI: 10.1186/s12894-016-0170-6
|View full text |Cite
|
Sign up to set email alerts
|

Rates of prostate surgery and acute urinary retention for benign prostatic hyperplasia in men treated with dutasteride or finasteride

Abstract: BackgroundPrevious studies have suggested a greater benefit for various outcomes in men diagnosed with benign prostatic hyperplasia (BPH) who are treated with dutasteride than for men treated with finasteride. This study investigates whether the rates of BPH-related prostate surgery and acute urinary retention (AUR) differ between dutasteride and finasteride users in the Netherlands.MethodsFrom the PHARMO Database Network, men aged ≥50 years with a dispensing of dutasteride or finasteride with or without conco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Benign prostatic hyperplasia (BPH) is the most common benign tumor in men . By 50 years of age, up to 50% of men may have histologically distinguished BPH with reported prevalence increasing to 90% by age 90 .…”
Section: Introductionmentioning
confidence: 99%
“…Benign prostatic hyperplasia (BPH) is the most common benign tumor in men . By 50 years of age, up to 50% of men may have histologically distinguished BPH with reported prevalence increasing to 90% by age 90 .…”
Section: Introductionmentioning
confidence: 99%
“…Data from five studies, which evaluated the long-term use of a1-blockers, showed that patients receiving a1-blockers had a significantly lower risk of recurrent AUR [14]. The use of 5a reductase inhibitors (5ARIs) as a combination therapy with a1-blockers in AUR treatment is still controversial [15,16]. Urgent prostatic surgery is another therapeutic option for AUR, however with a higher risk of intra-and/or postoperative complications and mortality than elective surgery [17].…”
mentioning
confidence: 99%
“…Finasteride inhibits only 5α‐reductase type 2, whereas dutasteride inhibits 5α‐reductase types 1 and 2 with similar potency . Subsequently, dutasteride induces a deeper suppression of serum DHT with respect to finasteride (90% vs 70%) . Moreover, dutasteride has a longer half‐life compared to finasteride (approximately 4 weeks vs 6 h) .…”
Section: Discussionmentioning
confidence: 99%
“…Until the early 90s, the choice of therapy in patients with LUTS/BPO consisted of either watchful waiting or surgical treatment. Currently, medical therapy is considered the first‐line option for men with moderate to severe LUTS/BPO . Four classes of drugs are available that can potentially improve BPO through various mechanisms of actions: alpha‐1 adrenergic antagonists (ABs), 5‐alpha reductase inhibitors (5‐ARIs), phosphodiesterase type 5 inhibitors (PDE5is), and phytotherapic compounds …”
Section: Introductionmentioning
confidence: 99%